In vivo splenic clearance correlates with In vitro deformability of red blood cells from plasmodium yoelii-infected mice - Huang, Sha (2015)
Recent experimental and clinical studies suggest a crucial role of mechanical splenic filtration in the host's defense against malaria parasites. Subtle changes in red blood cell (RBC) deformability, caused by infection or drug treatment, could influence the pathophysiological outcome. However, in vitro deformability measurements have not been directly linked in vivo with the splenic clearance of RBCs. In this study, mice infected with malaria-inducing Plasmodium yoelii revealed that chloroquine treatment could lead to significant alterations to RBC deformability and increase clearance of both infected and uninfected RBCs in vivo. These results have clear implications for the mechanism of human malarial anemia, a severe pathological condition affecting malaria patients.